A safe and effective management strategy for blunt cerebrovascular injury: Avoiding unnecessary anticoagulation and eliminating stroke. Issue 6 (June 2016) - Shahan, Charles P.; Magnotti, Louis J.; Stickley, Shaun M.; Weinberg, Jordan A.; Hendrick, Leah E.; Uhlmann, Rebecca A.; Schroeppel, Thomas J.; Hoit, Daniel A.; Croce, Martin A.; Fabian, Timothy C.
Abstract : BACKGROUND: Few injuries have produced as much debate with respect to management as have blunt cerebrovascular injuries (BCVIs). Recent work (American Association for the Surgery of Trauma 2013) from our institution suggested that 64-channel multidetector computed tomographic angiography (CTA) could be the primary screening tool for BCVI. Consequently, our screening algorithm changed from digital subtraction angiography (DSA) to CTA, with DSA reserved for definitive diagnosis of BCVI following CTA-positive study results or unexplained neurologic findings. The current study was performed to evaluate outcomes, including the potential for missed clinically significant BCVI, since this new management algorithm was adopted. METHODS: Patients who underwent DSA (positive CTA finding or unexplained neurologic finding) over an 18-month period subsequent to the previous study were identified. Screening and confirmatory test results, complications, and BCVI-related strokes were reviewed and compared. RESULTS: A total of 228 patients underwent DSA: 64% were male, with mean age and Injury Severity Score (ISS) of 43 years and 22, respectively. A total of 189 patients (83%) had a positive screening CTA result. Of these, DSA confirmed injury in 104 patients (55%); the remaining 85 patients (45%) (false-positive results) were found to have no injury on DSA. Five patients (4.8%) experienced BCVI-related strokes, unchanged from the previous study (3.9%, p = 0.756); two were symptomatic at trauma center presentation, and three occurred while receiving appropriate therapy. No patient with a negative screening CTA result experienced a stroke. CONCLUSION: This management scheme using 64-channel CTA for screening coupled with DSA for definitive diagnosis was proven to be safe and effective in identifying clinically significant BCVIs and maintaining a low stroke rate. Definitive diagnosis by DSA led to avoidance of potentially harmful anticoagulation in 45% of CTA-positive patients (false-positive results). No strokes resulted from injuries missed by CTA. LEVEL OF EVIDENCE: Diagnostic study, level III.